2022
DOI: 10.3390/ijms231911822
|View full text |Cite
|
Sign up to set email alerts
|

CTH/H2S Regulates LPS-Induced Inflammation through IL-8 Signaling in MAC-T Cells

Abstract: Hydrogen sulfide (H2S), as an endogenous gaseous signaling molecule, plays an important role in the inflammatory process. Our previous study found that Cystathionine-γ-lyase (CTH) and H2S are correlated with the occurrence and development of Clinical Mastitis (CM) in Holstein cows. However, the functions and regulatory mechanisms of CTH/H2S are still unknown. In this study, the inflammatory mammary cell model based on the MAC-T cell line was established by Lipopolysaccharide (LPS)-induced manner to further exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…The results showed that the value of serum Il-6 was significantly increased after XE treatment, and NaHS adding display marked decrease in serum IL-6 level. This data is consistent with previous reports(Lin et al, 2022) showed that H2S exhibited an antiinflammatory effect on various tissues and organs in mammals(Ali et al, 2018), vascular inflammation(Martelli et al, 2021), cardiovascular inflammation(Sikura et al, 2019;, and airway inflammation(Bazhanov et al, 2017). However,Sağlam et al (2017) showed that NaHS addition did not show any decrease in IL-6 levels.…”
supporting
confidence: 93%
“…The results showed that the value of serum Il-6 was significantly increased after XE treatment, and NaHS adding display marked decrease in serum IL-6 level. This data is consistent with previous reports(Lin et al, 2022) showed that H2S exhibited an antiinflammatory effect on various tissues and organs in mammals(Ali et al, 2018), vascular inflammation(Martelli et al, 2021), cardiovascular inflammation(Sikura et al, 2019;, and airway inflammation(Bazhanov et al, 2017). However,Sağlam et al (2017) showed that NaHS addition did not show any decrease in IL-6 levels.…”
supporting
confidence: 93%